High-resolution spectra of 2νOH overtone of trans-formic acid in the supersonic jet. (December 2022) - Svoboda, Vít; Rakovský, Jozef; Votava, Ondrej
Highlights: We use a direct laser absorption spectroscopy combined with a slit nozzle to generate a supersonic expansion of trans-formic acid. By using this experimental scheme, absorption spectra at temperature of 37 K were measured thus complementing the only high-resolution room temperature FTIR spectra available in the literature (Hurtmans et al., JCP 113 (2000), 1535), published more than 20 years ago (!). Our approach provides a significant simplification of the measured spectra as compared to the FTIR due to rotational cooling leading to depopulation of higher rotational states. A better resolution of our spectra is achieved due to Doppler narrowing of absorption lines in the supersonic expansion. The data are analyzed using a newly developed line-by-line assignment software based on the extended concept of ground state combination differences (GSCD). This approach takes an advantage of low-line density and high frequency-calibration precision of the jet-cooled spectra. Following the above-mentioned assignment procedure, reliable line assignments were obtained forming a high-precision map of 39 upper rotational states of the 2 ν OH vibration. Their assignment to the overtone vibration was checked by a global fitting using an effective Hamiltonian. The global fitting provided spectroscopic constants for the 2 ν OH vibration. These are critically compared to those previously obtained by Hurtmans et al. In addition, the global fit allowed to visualize positions of perturbations connecting the primary overtone vibration to the bath of dark states in this spectral region. Abstract: First high-resolution low-temperature spectrum of the 2 ν OH overtone of trans -formic acid have been measured using direct-absorption laser spectroscopy. The supersonic cooling in the jet expansion to 37 K has dramatically simplified the complex ro-vibrational structure of the band due to the thermal depopulation of higher-lying rotational states. Altogether, 597 lines have been measured with a line-position accuracy better than 0.001 cm − 1, and 441 of them have been reliably assigned using a custom-build program for a line-by-line assignment using the ground state combination differences. In total, 39 low-lying upper rotational states of the overtone vibration have been calculated from these line assignments. Moreover, some additional states have been also identified and tentatively assigned to a bath of dark states present in this spectral region. A global fit using A-reduced Watson's type Hamiltonian in I r representation has been performed to obtain several ro-vibrational constants for the 2 ν OH vibration. In addition, the fit demonstrates the effect of numerous perturbations in the rotational structure.